2019
DOI: 10.1002/soej.12364
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Associations between SNAP and Food Insecurity, Obesity, and Food Purchases with Imperfect Administrative Measures of Participation

Abstract: Administrative data are considered the “gold standard” when measuring program participation, but little evidence exists on their potential problems or implications for econometric estimates. We explore these issues using the FoodAPS, a unique data set containing two different administrative measures of Supplemental Nutrition Assistance Program (SNAP) participation and a survey‐based measure. We document substantial ambiguity in the two administrative measures and show that they disagree with each other almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…In addition, studying geographic variation in survey error requires the accuracy of the linked administrative variable not to vary between states. Courtemanche et al (2018) show that variation between states also stems from differences in data quality or linkage rather than from differences in reporting only. For the sample we use, we have no evidence of systematic differences in the accuracy of the linked data between states.…”
Section: Administrative Records and Data Linkagementioning
confidence: 93%
See 1 more Smart Citation
“…In addition, studying geographic variation in survey error requires the accuracy of the linked administrative variable not to vary between states. Courtemanche et al (2018) show that variation between states also stems from differences in data quality or linkage rather than from differences in reporting only. For the sample we use, we have no evidence of systematic differences in the accuracy of the linked data between states.…”
Section: Administrative Records and Data Linkagementioning
confidence: 93%
“…Consequently, we only analyze data from the 13 states that provided the most accurate and homogeneous data to minimize confounding survey error with variation in administrative data and linkage quality. 4 Courtemanche et al (2018) and Kang and Moffitt (2018) use the data from all states and examine their accuracy and usefulness further. They also find differences in the linked administrative variable between the 13 states that provided caseload and ALERT data with unique IDs and the remaining states.…”
Section: Administrative Records and Data Linkagementioning
confidence: 99%
“…MEPS queries subjects about whether they received an EITC refund but not the amount, and numerous prior studies have shown that self-reported receipt of EITC and other welfare benefits is neither sensitive nor specific and may bias results. [37][38][39][40] We therefore assumed that all individuals received the refund for which they were eligible, which is analogous to an intentto-treat approach in a randomized controlled trial. Prior work has shown that approximately 80 percent of eligible individuals during this time period received their refunds, 41 which means that this technique suffers from a degree of misclassification.…”
Section: Exposurementioning
confidence: 99%
“…Using ALERT, a household is considered to be a true current SNAP participant if the matching procedure indicated a disbursement during a 36-day window before the survey date. Courtemanche, Denteh, and Tchernis (2018), among other researchers, point out limitations of SNAP administrative records employed in FoodAPS, including missing data and varying degree of data quality across states. Also, the two administrative data sources sometimes disagree, perhaps in part due to underlying timing discrepancies.…”
Section: Analytical Samplementioning
confidence: 99%